Dini ve Kültürel Çoğulculukta Varoluş Mücadelesine Bir Bakış: Malezya Tecrübesi / An Overview towards the Existence Struggle in Religious and Cultural Pluralism: Malaysia Experience - Kayadibi, Saim (Journal of History Culture and Art Research, 2016)
An Overview towards the Existence Struggle in Religious and Cultural Pluralism: Malaysia Experience Abstract Malaysia with its socio-cultural structure is one of the rare unity that can exemplify many countries because of her ability to live in peace and tranquillity with multi-religious, multilingual and multicultural societies. Considering this multi-culturalism, multi-religion and multi-lingual as a wealth, thus they are struggling together to create a strong society. In many fields such as Islamic economy, banking, and halal food, she is able to play a pioneering role in the application of Islamic law in a modern state, yet it has many momentous works in the race to become a central country. In terms of historical experience, with her strategical position, Malaysia has been the centre of serious occupations, thus it has been struggling to get rid of the traces of many colonial states, colonial psychology and trying to wrap their wounds. Despite the bitter memories of the colonial countries in the past, brotherly and friendly aids she has seen from the Ottoman State left a firm mark on the depths of her memory. Now, it’s struggling to carry together with different ethnic structures to the future in harmony and peace in which she has a model structure that can set an example for other countries. However, trying to compare Malaysia with Turkey may cause incorrect consequences. It is unthinkable comparing Turkey, which has no colonial past and has a relatively low population of non-Muslims, with Malaysia. In this article, Malaysia will be taken as an example while Muslims are examined in highly religious societies and their lives, historical and social stages, whether there are any problems in the practices of religious life, in order to create a national consciousness what kind of strategies have been developed, through a holistic approach the problems, and their solutions will be discussed. Dini ve Kültürel Çoğulculukta Varoluş Mücadelesine Bir Bakış: Malezya Tecrübesi Öz Malezya sosyo-kültürel yapısı itibari ile çok dinli, çok dilli ve çok kültürlü toplumların barış ve huzur içerisinde yaşayabilme özelliğini göstermesinden dolayı birçok ülkeye örnek oluşturabilecek nadide birlikteliklerden biridir. Bu çok kültürlülük, çok dinlilik ve çok dillilik özelliklerini bir zenginlik olarak görüp, birlikte güçlü bir toplum oluşturabilmenin çabası içerisindedir. Birçok sahada, örneğin İslam Ekonomisi ve Bankacılığı, Helal Gıda, modern bir devlette İslam Hukuku kurallarının uygulanabilme özelliğinde öncü rol oynayabilen, hatta merkez ülke olma yarışında ciddi çalışmaları vardır. Tarihi tecrübe açısından Malezya, konum itibariyle ciddi işgallerin merkezi olmuş, birçok sömürge devletinin izlerini atabilmenin, sömürge psikolojisinden kurtulabilmenin, yaralarını sarabilmenin mücadelesini veren bir ülkedir. Geçmişte sömürge ülkelerinden kalan acı hatıraya rağmen Osmanlı devletinden gördüğü kardeş ve dost yardımlar hafızasının derinliklerinde sağlam izler bırakmıştır. Şimdi ise farklı etnik yapısını huzur ve barış içerisinde birlikte götürebilmenin mücadelesini veren ve diğer ülkelere de örnek oluşturabilecek model bir yapıya sahiptir. Bunun yanında Malezya’yı Türkiye ile karşılaştırmaya çalışmak yanlış sonuçlar doğurabilir. Sömürge geçmişi olmayan, gayr-i Müslim nüfusu neredeyse yok denecek kadar az olan Türkiye’nin Malezya ile kıyaslanması düşünülemez. Bu makalemizde çok dinli toplumlarda Müslümanlar incelenirken Malezya örnek olarak alınacak, onların yaşamları, tarihi ve sosyal evreleri, dini hayatın yaşanmasında sorunların olup olmadığı, milli bir bilinç oluşturmak için nasıl bir strateji geliştirildiği, topyekûn bir bakış açısı ile problemlerin neler olduğu ve ne tür çözüm yolları geliştirildiği gibi konular üzerinde durulacaktır.